WANITA DAN PEMBINAAN MORAL (Suatu Analisis Filsafat Akhlak) - Masse, Rahman Ambo (AL-MAIYYAH, 2016)
This article considers the concept of moral philosophy associated with the development of modern ethics. Through literature review, found that the studies of moral philosophy tend to stagnate. Moral philosophy which comes from the revelation, the most universal source of value, should be the guideline of human life. However, the values listed in the Quran has not been actualized properly as it should be due to the dominance of Muslim thinking is more focused on the dimension of aqidah and syariah. Moral thinking listed in the Quran should not only on the axiology level as a grand theory, but also on the epistemology level which emphasis on the ethical-anthropological dimension without leaving the theological dimension.